THE INFLUENCE OF ACCOUNTABILITY TRANSPARENCY AND AMIL LITERACY ON MUZAKKI'S TRUST IN PAYING ZAKAT IN PALOPO CITY (Empirical Study of BAZNAS Palopo City) - Fachri, Andi Muhammad; Usman, Halim; Sahrir, Sahrir (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
Baznas that has good accountability, good transparency and good amil literacy so that it can be conducive tends to be able to increase muzakki trust effectively. The purpose of this study is to evaluate how muzakki trust is influenced by accountability, transparency, and amil literacy. Muzakki in Palopo City became the research population totaling 115 respondents, and a sample of the entire population was taken. Online questionnaires were used to collect primary data for this quantitative research. which were analyzed using the SPSS 25 application, using data analysis approaches such as instrument testing, multiple linear regression testing, and hypothesis testing. The t-test results show that accountability has a significant and positive effect on muzakki trust. In addition, transparency and amil literacy have a positive effect. Meanwhile, the f-test shows that simultaneously, accountability, transparency, and amil literacy have a positive and significant effect on muzakki trust